La comunicación y su incidencia en la resolución de conflictos laborales - Portilla Aviles, Ericka Lisbeth (2019)
The present case study was carried out with the theme: communication and its incidence in the resolution of labor disputes in the officials of the Department of General Secretariat of the Rural Parish Decentralized Autonomous Government of Ricaurte; which is a government, organization for the development of this analysis the deductive method was used because it allowed to obtain generals knowledges from particular facts, through the application of a survey that helped to gather relevant and necessary information, whose objective is to determine the incidence of communication in the resolution of labor disputes. The results obtained in this study show that not mastering communication skills or abilities affect the organizational climate of the institution which causes demotivation and disagreement, reason why administrative processes are not comply fullness since in the professional environment, strengthening work relationships helps to maintain an adequate organizational environment and allows staff to establish effective communication, therefore it can be concluded that communication is an essential and strategic component on which all the activity carried out inside and outside the institution is based since the proper functioning of this is related in large part to the effectiveness and efficiency with its collaborators developed in some activity